Problems and challenges encountered by Chinese medical institutions in implementing the national centralized drug procurement - Zhang, Wen; Xu, Qingwen; Peng, Jing; Zhang, Xiaotong; Chen, Lu; Wu, Yilai; Yang, Kui; Luan, Jiajie; Liu, Xiaoyun (Frontiers in Pharmacology, 2023)
The problems and challenges encountered by Chinese medical institutions in implementing the national centralized drug procurement was investigated and analyzed in order to provide reference for the regulatory agencies to formulate policies.A questionnaire survey was conducted to collect the problems encountered by 329 Chinese medical institutions in implementing the national centralized drug procurement and the corresponding suggestions provided by relevant experts. Statistical analysis was performed to identify differences in the themes and the number of collected problems, further revealing the relevance of both to the region in which the medical institutions is located.Result: 1360 problems and suggestions were collected from 329 Chinese medical institutions that located in North (19.15%), Northeast (5.78%), East (33.43%), Central (10.03%), South (9.73%), Southwest (14.89%), and Northwest China (6.99%). There was statistically significant difference in the number of collected problems and suggestions between regions (P<0.001). Furthermore, the content of gathered problems and suggestions involves in 15 themes including system construction, organizational system and work responsibilities, reasonable measurement et al.. These themes that these medical institutions are focusing on are mainly centered on the supply guarantee (15%), reasonable measurement and reporting of procurement volume (11.40%) and guarantee measures for clinical priority use (9.48%) of drugs with national centralized procurement. Meanwhile, we found that problems regarding the supply guarantee of drugs with national centralized procurement displayed significant difference between regions (P=0.0096).Chinese medical institutions are facing great challenges in implementing the national centralized drug procurement. The scientific study and judgment of the current situation and the construction of corresponding solution require a precise classification of the problems encountered by medical institutions in the process of implementing the national centralized drug procurement policy, which is of great practical significance for deepening the reform of the medical and health system.